Two Extremely Preterm Infants Discharged with a Home High-Flow Nasal Cannula for Severe Bronchopulmonary Dysplasia - Yuichi Kubo; Takuya Tokuhisa; Hiroshi Ohashi (Hindawi Limited, 2024)
Home high-flow nasal cannula (HFNC) use in the neonatal field has become prevalent as a noninvasive respiratory support, but its application in home care remains rare. We report two cases in which a home HFNC was effective in managing extremely low-birth-weight infants with severe bronchopulmonary dysplasia (BPD). Case 1 was a male infant born at 22 weeks' gestation weighing 435 g. Case 2 was a female infant born at 23 weeks' gestation weighing 450 g. Both patients had mothers with chronic placental abruption or chorioamnionitis. They transitioned from invasive mechanical ventilation to nasal CPAP (nCPAP) at 45 days (case 1) and 50 days (case 2) old. Subsequently, at 324 days (case 1) and 90 days (case 2) old, they transitioned to a HFNC, demonstrating stable oxygenation and ventilation, but faced difficulty in removal. Considering the drawbacks of prolonged hospitalization, the patients were discharged using a home HFNC at 404 days (case 1) and 391 days (case 2) old. For case 1, the HFNC was set at 4 L/min of room air and 2 L/min of oxygen, whereas for case 2, it was set at 5 L/min of room air and 1 L/min of oxygen. These settings maintained an SpO2 above 90% and a pCO2 below 60 mmHg. An HFNC offers advantages over nCPAP owing to its lower invasiveness and reduced discomfort for long-term use. However, reports on the use of a home HFNC for BPD are scarce. In recent years, while premature infant mortality has decreased worldwide, the incidence of BPD has risen, necessitating preparedness for prolonged ventilation in preterm infants. Home ventilators represent a strategy to prevent extended hospitalization, and based on our cases, home HFNC for BPD appears safe and effective, making it potentially useful for managing preterm infants requiring prolonged respiratory support in the future.